Nerve ultrasound findings in Sjögren's syndrome‐associated neuropathy. Issue 6 (16th July 2021) - Seeliger, Tabea; Bönig, Lena; Gingele, Stefan; Prenzler, Nils K.; Thiele, Thea; Ernst, Diana; Witte, Torsten; Stangel, Martin; Skripuletz, Thomas; Körner, Sonja
Abstract: Background and Purpose: The phenotype of Sjögren's syndrome‐associated neuropathy has been better characterized in recent years. However, Sjögren's syndrome‐associated neuropathy remains an underdiagnosed entity with only few insights considering the pathomechanisms of nerve damage. Nerve ultrasound has proven to be a useful and efficient tool in detecting nerve damage of autoimmune origin. We, therefore, aimed to evaluate this method for Sjögren's syndrome‐associated neuropathy. Methods: Patients with Sjögren's syndrome and clinical signs of neuropathy underwent sonographic examination of both median and ulnar nerves. Nerve thickening was classified for cross‐sectional areas of >12 mm² at the median nerve and for >10 mm² at the ulnar nerve. Fascicle thickening was documented for cross‐sectional areas ≥5 mm² at the median and ≥3 mm² at the ulnar nerve. Results: Forty‐three patients were included in the analysis (median age 60 years [interquartile range 53–73 years], female rate 60%). 31/43 patients (72%) showed abnormalities on nerve ultrasound, while nerve thickening was found more frequently than fascicle thickening (90% vs. 52% of patients with sonographic abnormalities, respectively). Abnormal findings were observed more frequently at the median nerve and in proximal localization. Abnormal findings on nerve conduction studies were evident in 36/43 patients (84%). Nerve conduction studies revealed a tendency of demyelinating nerve damage patterns being associated with abnormal findings on nerve ultrasound. Conclusions: In addition to nerve conduction studies, nerve ultrasound may have a supporting role in the diagnosis of Sjögren's syndrome‐associated neuropathy. Also, our data support an immune‐mediated inflammatory demyelinating pathogenesis of Sjögren's syndrome‐associated neuropathy.